2020
DOI: 10.1002/ajh.25915
|View full text |Cite
|
Sign up to set email alerts
|

Localized immunoglobulin light chain amyloidosis: Novel insights including prognostic factors for local progression

Abstract: In localized light chain amyloidosis (locAL), amyloidogenic light chains (aLC) are produced and deposited locally by a B‐cell clone. We present 293 patients with immunohistochemically confirmed locAL. Lung (nodular pulmonary) with 63 patients was the most involved organ. The aLC was λ in 217 cases (κ:λ ratio 1:3). A local B‐cell clone was identified in 30% of cases. Sixty‐one (21%) had a concomitant autoimmune disorder (cAD). A monoclonal component (MC) were present in 101 (34%) patients and were more frequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 38 publications
0
60
0
5
Order By: Relevance
“…In contrast, localized deposition of LCs causes nodules to develop in the skin and in the respiratory, urinary, and gastrointestinal tracts, with local symptoms and a benign course that usually is managed with local treatment. 1 In systemic AL amyloidosis, the PC clone is usually small (median infiltrate, 10%), and presents t (11;14) and gain 1(q21) in ∼50% and 20% of clones, respectively, whereas high-risk aberrations are uncommon. 2,3 Patients whose PC clones harbor t (11;14) have a worse outcome with bortezomib and immunomodulatory drugs (IMiDs), whereas gain 1(q21) is associated with poorer results with oral melphalan.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, localized deposition of LCs causes nodules to develop in the skin and in the respiratory, urinary, and gastrointestinal tracts, with local symptoms and a benign course that usually is managed with local treatment. 1 In systemic AL amyloidosis, the PC clone is usually small (median infiltrate, 10%), and presents t (11;14) and gain 1(q21) in ∼50% and 20% of clones, respectively, whereas high-risk aberrations are uncommon. 2,3 Patients whose PC clones harbor t (11;14) have a worse outcome with bortezomib and immunomodulatory drugs (IMiDs), whereas gain 1(q21) is associated with poorer results with oral melphalan.…”
Section: Introductionmentioning
confidence: 99%
“…4 Concomitant autoimmune disorders are commonly associated with localized cutaneous amyloidosis. 5 Of note, up to 25% of NLPCA cases are reported with co-occurring Sjogren syndrome but the nature of this association is unclear. 6 Other autoimmune diseases, including CREST syndrome and primary biliary cirrhosis may also present alongside NLPCA.…”
Section: Discussionmentioning
confidence: 99%
“…In their analysis of 293 patients with localized AL amyloidosis (locAL), Basset et al reported lower respiratory tract involvement in 10.6% of the cases, as well as a 5-year progression free survival rate of 80%. In their study, 16 patients died during a median follow-up of 44 months, all of whom exhibited respiratory tract involvement (nine with lung involvement, four with lower airway involvement, and three with locAL in the nasopharynx) (24). Local tracheobronchial AL amyloidosis seems to be heterogeneous, with symptoms and concomitant disorders having the potential to affect prognosis.…”
Section: Discussionmentioning
confidence: 99%